×

# A Trigonometric Geometric Sequence

Evaluate

$\sum_{k=1}^n \frac{1}{ \sin \left( \frac{ 2^k \pi} { 2^{n+1} -1} \right) }.$

In particular, show that

$\frac{ 1}{ \sin ( \frac{2\pi}{7} )} + \frac{1}{ \sin( \frac { 4 \pi } { 7} )} = \frac{1}{ \sin ( \frac{\pi}{7} ) }.$

This question is prompted by Daniel's Arc Co Tangent Sum.

Hint: Telescoping Series

Note by Calvin Lin
2 years, 7 months ago

## Comments

Sort by:

Top Newest

Since

$$\csc 2x=\cot x-\cot 2x$$

the sum can be written as:

$$\displaystyle \sum_{k=1}^n \frac{1}{\sin\left(\frac{2^k\pi}{2^{n+1}-1}\right)}=\sum_{k=1}^n \left(\cot\left(\frac{2^{k-1}\pi}{2^{n+1}-1}\right)-\cot\left(\frac{2^k\pi}{2^{n+1}-1}\right) \right)$$

$$\displaystyle =\cot\left(\frac{\pi}{2^{n+1}-1}\right)-\cot\left(\frac{2^n\pi}{2^{n+1}-1}\right)=\cot\left(\frac{2^{n+1}\pi}{2^{n+1}-1}\right)-\cot\left(\frac{2^n\pi}{2^{n+1}-1}\right)$$

$$\displaystyle =-\csc\left(\frac{2^{n+1}\pi}{2^{n+1}-1}\right)=\boxed{\csc\left(\dfrac{\pi}{2^{n+1}-1}\right)}$$

For $$n=2$$, it can be shown that:

$$\displaystyle \csc\left(\frac{2\pi}{7}\right)+\csc\left(\frac{4\pi}{7}\right)=\csc\left(\frac{\pi}{7}\right)$$ · 2 years, 7 months ago

Log in to reply

Good job! I couldn't notice that! · 2 years, 7 months ago

Log in to reply

May be the part 2 of question is inspired from a question of IIT JEE 2011 . Am I correct ? · 2 years, 7 months ago

Log in to reply

I came across it in a different context, where it was given as a specific case of the first result. Staff · 2 years, 7 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...